Critical dimension for the dislocation structure in deformed copper micropillars. (1st April 2019) - Zhao, X.X.; Wu, J.; Chiu, Y.L.; Jones, I.P.; Gu, R.; Ngan, A.H.W.
Abstract: Although the effect of specimen size on strength has been well documented for metal micro-samples significantly larger than 1 μm, less is known about the deformation induced dislocation structure, especially just above the size at which dislocation starvation happens. Here, uniaxial compression tests were performed on cylindrical [011] oriented copper micropillars with diameters of 1 μm, 3 μm and 5 μm. Dislocation cells formed in a fractal geometry in the 3 μm and 5 μm pillars, while dislocations were not retained in the 1 μm pillars. The effects of strain and strain rate on cell formation were also investigated. Graphical abstract: Unlabelled Image